Modification of C Terminus Provides New Insights into the Mechanism of α-Synuclein Aggregation - Afitska, Kseniia; Fucikova, Anna; Shvadchak, Volodymyr V; Yushchenko, Dmytro A (Biophysical journal, 2017)
Aggregation of neuronal protein α-synuclein leads to the formation of amyloid fibrils, which are associated with the development of Parkinson's disease. The mechanism of α-synuclein pathology is not fully understood and is a subject of active research in the field. To tackle this problem, the fusions of fluorescent proteins to α-synuclein C-terminus are often used in cellular and animal studies. The effects induced by such α-synuclein sequence extension on α-synuclein aggregation propensity are, however, not systematically examined despite the evidence that the negatively charged C-terminus plays a critical role in the regulation of α-synuclein aggregation. In this work, we investigated how the charge and length variations of the C-terminus affect the aggregation propensity of α-synuclein. To address these questions, we prepared mutants of α-synuclein carrying additional moieties of different charge and length at the protein C-terminus. We determined the rates of two different aggregation stages (primary nucleation and elongation) based on a thioflavin T kinetic assay. We observed that all mutants bearing neutrally charged moieties of different length fibrilized slower than wild-type α-synuclein. The primary nucleation and elongation rates strongly decreased with increase of the C-terminal extension length. Meanwhile, charge variation of the C-terminus significantly changed the rate of α-synuclein nucleation, but did not markedly affect the rate of fibril elongation. Our data demonstrate that both the charge and length of the C-terminus play an important role at the stage of initial fibril formation, but the stage of fibril elongation is affected mainly by the length of C-terminal extension. In addition, our results suggest that there are at least two steps of incorporation of α-synuclein monomers into the amyloid fibril: namely, the initial monomer binding to the fibril end (charge-dependent, relatively fast), and the subsequent conformational change of the protein (charge-independent, relatively slow, and thus the rate-limiting step).
Keywords: mutace; alfa-synuklein; vztah mezi dávkou a účinkem léčiva; alpha-Synuclein; Kinetics; Dose-Response Relationship, Drug; soli; Salts; Mutation; proteinové agregáty; kinetika; Protein Aggregates